2017
DOI: 10.5056/jnm16153
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Gastric Emptying and Gastric Adaptive Relaxation Influenced by Amino Acids

Abstract: Background/AimsAmino acids have many physiological activities. We report the correlation between gastric emptying and gastric adaptive relaxation using tryptophan and amino acids with a straight alkyl chain, hydroxylated chain, and branched chain. Here we sought to further clarify the correlation between gastric emptying and gastric adaptive relaxation by using other amino acids. MethodsIn Sprague-Dawley rats, gastric emptying was evaluated by a breath test using [1-13 C] acetic acid. The expired 13 CO 2 patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…In vivo assessment of natural GI functions in small animals is more challenging given their smaller body size, much faster gastric motility, and the need for voluntary meal consumption. Existing methods are often invasive (or even lethal), radioactive and indirect, or employ other imaging methods that offer limited spatial, temporal, or quantitative resolution. For example, the gastric barostat method requires intubation of a balloon in the proximal or distal stomach to measure gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo assessment of natural GI functions in small animals is more challenging given their smaller body size, much faster gastric motility, and the need for voluntary meal consumption. Existing methods are often invasive (or even lethal), radioactive and indirect, or employ other imaging methods that offer limited spatial, temporal, or quantitative resolution. For example, the gastric barostat method requires intubation of a balloon in the proximal or distal stomach to measure gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…In-vivo assessment of natural GI functions in small animals is more challenging given their smaller body size, much faster gastric motility, and the need for voluntary meal consumption. Existing methods are often invasive (or even lethal) (48), radioactive (49) and indirect (50), or employ other imaging methods (51) that offer limited spatial, temporal, or quantitative resolution. For example, the gastric barostat method requires intubation of a balloon in the proximal or distal stomach to measure gastric motility.…”
Section: Naturalistic Feeding Protocol and Non-invasive Imaging Ensurmentioning
confidence: 99%
“…Secretion of gastric acid facilitates the degradation of proteins into amino acids, which may contribute to the satiating effect of proteins. Dietary l ‐arginine, i.e., has been shown to reduce energy intake in rodents and to delay and inhibit gastric emptying . Furthermore, we recently demonstrated that l ‐arginine stimulated mechanisms of GAS and increased the release of serotonin in a parietal cell model.…”
Section: Introductionmentioning
confidence: 79%
“…[48] A delay in gastric emptying is known to promote early satiety. [49] However, evidence for l-arginine's effect on gastric emptying in humans is still conflicting, by describing a delay [17,50] on the one hand, and an accelerated gastric emptying [51] on the other, which may be due to application of different detection methods and study models. In addition, proteins differentially regulate gastric emptying depending on their origin, with a mostly increased gastric emptying for whey protein in comparison to cod, gluten, or casein, when administrated within a standardized test meal in an amount of 45 g. [14] In the present human intervention study, both the WPH as well as the WPH + ARG intervention delayed gastric emptying, which was analyzed using 13 C-Na-acetate as a marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation